Sosialisasi Program Edukasi dan Keterampilan Dasar di Lembaga Kesejahteraan Sosial Anak (LKSA) di Panti Asuhan Caritas Dorkas - Sukaaro Waruwu; Angel Catherina Justice Zebua; Arisman Zai; Asmiarni Putri Dawolo; Tatrianti Zai; Syukur Niatman Ndruru; Johan Kosman Zai; Kristiani Waruwu; Restu Oktavianus Zai; Ohani Jon Waruwu (Lembaga Pengembangan Kinerja Dosen, 2025)
Children under the care of the Child Welfare Institution (LKSA) generally come from vulnerable backgrounds, such as losing their parents, poverty, or neglect, which limits their access to education and character building. This Community Service Activity (PKM) aims to enhance educational awareness, learning motivation, and basic life skills among children at the LKSA Caritas Dorkas Orphanage. The methods employed include interactive lectures, educational games, simple simulations, and creative activities. The results of the activity showed an increase in children's understanding of the importance of education, the growth of learning enthusiasm, and the development of positive behaviors such as cooperation, responsibility, and personal hygiene. Life skills simulations successfully fostered new, more productive habits, while creative activities encouraged children's expression and self-confidence. In conclusion, the educational-participatory approach was able to create positive psychosocial and behavioral impacts. The implications of this activity indicate that simple yet structured interventions in the LKSA environment can be an effective strategy in building children's character and independence. Such activities need to be carried out continuously and involve various parties to strengthen the role of LKSA as a holistic and transformative childcare institution.